Proportion of alemtuzumab-treated patients converting from relapsing-remitting multiple sclerosis to secondary progressive multiple sclerosis over 6 years - Horáková, Dana; Boster, Aaron; Bertolotto, Antonio; Freedman, Mark S; Firmino, Isabel; Cavalier, Steven J; Jacobs, Alan K; Thangavelu, Karthinathan; Daizadeh, Nadia; Poole, Elizabeth M; Baker, Darren P; Margolin, David H; et al. (Multiple sclerosis journal - experimental, translational and clinical, 2020)
BACKGROUND: Few data exist concerning conversion to secondary progressive MS in patients treated with disease-modifying therapies. OBJECTIVE: Determine the proportion of alemtuzumab-treated patients converting from relapsing-remitting to secondary progressive MS during the CARE-MS core and extension studies. METHODS: Patients (N = 811) were analyzed post hoc for secondary progressive MS conversion. Optimal conversion definition: Expanded Disability Status Scale (EDSS) score ≥4, pyramidal functional system score ≥2, and confirmed progression over ≥3 months including confirmation within the functional system leading to progression, independent of relapse. RESULTS: Over 6.2 years median follow-up, 20 alemtuzumab-treated patients converted (Kaplan-Meier estimate, 2.7%; 95% confidence interval, 1.8%-4.2%). Sensitivity analysis accounting for dropouts showed similar results (3%), as did analyses using alternative definitions with different EDSS thresholds and/or confirmation periods, and analysis of core study subcutaneous interferon beta-1a-treated patients who received alemtuzumab in the extension. Patients converting to secondary progressive MS were older, and had higher EDSS scores and greater brain lesion volumes at baseline, but did not need additional alemtuzumab or other therapies. CONCLUSIONS: The 6-year conversion rate to secondary progressive MS was low for alemtuzumab-treated patients, supporting further study of the role alemtuzumab may play in reducing risk of secondary progression.ClinicalTrials.gov identifiers: NCT00530348, NCT00548405, NCT00930553.
Keywords: secondary progressive multiple sclerosis; alemtuzumab; disease progression; Relapsing-remitting multiple sclerosis